2005
DOI: 10.1073/pnas.0501971102
|View full text |Cite
|
Sign up to set email alerts
|

Melanin photoprotection in the human retinal pigment epithelium and its correlation with light-induced cell apoptosis

Abstract: Time-resolved electron paramagnetic resonance (TREPR) spectroscopy was used to study melanin free radicals in human retinal pigment epithelium (RPE) cells and tyrosine-derived synthetic melanin. TREPR signal traces from RPE cells reveal in vivo light-induced melanin free radical photochemistry in more detail than previously known. Electron spin polarization reflecting a non-Boltzmann population within the energy levels of the spin system is observed in RPE cells as the result of the triplet state photoproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
95
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 55 publications
3
95
1
3
Order By: Relevance
“…Blue light has been shown to induce production of reactive oxygen species (ROS) in RPE cells, 7 triggering apoptosis. 8 The indole melatonin (N-acetyl-5-methoxytryptoamine) is a neurohormone that has crucial roles in the regulation of many physiological events. 9 It is a highly lipophilic molecule that can easily pass through the cell membranes and reach subcellular compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Blue light has been shown to induce production of reactive oxygen species (ROS) in RPE cells, 7 triggering apoptosis. 8 The indole melatonin (N-acetyl-5-methoxytryptoamine) is a neurohormone that has crucial roles in the regulation of many physiological events. 9 It is a highly lipophilic molecule that can easily pass through the cell membranes and reach subcellular compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolically, RPE cells are highly active and contain large numbers of mitochondria (1). Blue light induces the production of reactive oxygen species (ROS) in the mitochondria of RPE cells (15) and has been shown to lead to cell apoptosis (14), potentially triggered by ROS damage to mtDNA (16). It has also been suggested that the accumulation of ROS-induced damage during one's lifetime contributes not just to RPE loss but also to the overall aging process (17).…”
mentioning
confidence: 99%
“…Blue light is especially harmful (9) and produces light-induced apoptosis of rat RPE cells by a free radical mechanism (10). Although lipofuscin involvement in blue light-induced RPE loss could be important in aged RPE (11)(12)(13), fetal RPE are also susceptible to blue light-induced apoptosis (BLIA) (14). Metabolically, RPE cells are highly active and contain large numbers of mitochondria (1).…”
mentioning
confidence: 99%
See 2 more Smart Citations